In Vivo Sub-chronic Treatment with Dichlorvos in Young Rats Promotes Synaptic Plasticity and Learning by a Mechanism that Involves Acylpeptide Hydrolase Instead of Acetylcholinesterase Inhibition. Correlation with Endogenous β-Amyloid Levels - García-Rojo, Gonzalo; Gámiz, Fernando; Ampuero, Estíbaliz; Rojas-Espina, Daniel; Sandoval, Rodrigo; Rozas, Carlos; Morales, Bernardo; Wyneken, Ursula; Pancetti, Floria (Frontiers in Pharmacology, 2017)
Acylpeptide hydrolase (APEH) is a serine hydrolase that displays two catalytic activities, acting both as an exopeptidase toward short N-acylated peptides and as an endopeptidase toward oxidized peptides or proteins. It has been demonstrated that this enzyme can degrade monomers, dimers, and trimers of the A1–40 peptide in the conditioned media of neuroblastoma cells. In a previous report, we showed that the specific inhibition of this enzyme by the organophosphate molecule dichlorvos (DDVP) triggers an enhancement of long-term potentiation in rat hippocampal slices. In this study, we demonstrate that the same effect can be accomplished in vivo by sub-chronic treatment of young rats with a low dose of DDVP (0.1 mg/kg). Besides exhibiting a significant enhancement of LTP, the treated animals also showed improvements in parameters of spatial learning and memory. Interestingly, higher doses of DDVP such as 2 mg/kg did not prove to be beneficial for synaptic plasticity or behavior. Due to the fact that at 2 mg/kg we observed inhibition of both APEH and acetylcholinesterase, we interpret that in order to achieve positive effects on the measured parameters only APEH inhibition should be obtained. The treatment with both DDVP doses produced an increase in the endogenous concentration of A1–40, although this was statistically significant only at the dose of 0.1 mg/kg. We propose that APEH represents an interesting pharmacological target for cognitive enhancement, acting through the modulation of the endogenous concentration of A1–40.